H5, voir la French touch 30 ans de graphisme et de musique électronique - Bailey, David 1938-; Bernier, Alexis; Crecy, Etienne de; Houplain, Ludovic; Mirwais 1960- (Bernard Chauveau édition, 2024)
The Espace Richaud is home to H5, a French studio dedicated from the outset to the artistic direction of French touch musicians. This electronic music movement of the 2000s left its mark not only on its own era, but also on Versailles. Indeed, the town is home to a number of artists who were born and trained here. Almost 25 years and hundreds of collaborations later, a veritable collection has formed. Here, H5 brings out its treasures: 250 vinyl sleeves, videos, posters and flyers, forming a collection that reflects the golden age of Versailles. Authors David Bailey, Alexis Bernier, Étienne de Crécy, Ludovic Houplain and Mirwais tell the story of Studio H5 through interviews, playlists, etc. A book for those nostalgic for the dancefloors of the 1990s and 2000s, and for lovers of graphic design! Founded by Ludovic Houplain and Antoine Bardou-Jacquet in 1994, H5, which celebrates its 30th anniversary this year, has since established itself as a creative laboratory of excellence at the crossroads of graphic design, art direction, music videos and animated films. While the studio has also made a name for itself in the luxury, cultural and fashion sectors, its history remains intimately linked to that of the French touch
Frontispizseite: Cet ouvrage a été publié à l'occasion de l'exposition "H5. Voir la French touch. 30 ans de graphisme et de musique électronique" à l'espace Richaud de Versailles et dans le cadre du festival ElectroChic #8 en mars 2024. - Genaue Ausstellungsdaten ermittelt: Du 7 mars au 5 mai 2024
Keywords: H5 -- Firma; Geschichte 1999-2023; Geschichte 1995-2024; Grafikdesign; Animationsfilm; H5 / Expositions; Arts graphiques / France / 2000-....; Pochettes de disques; Ausstellungskatalog -- Espace Richaud -- 07.03.2024-05.05.2024 -- Versailles; Bildband